2015
DOI: 10.1002/etc.3216
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical occurrence in groundwater and surface waters in forests land‐applied with municipal wastewater

Abstract: The occurrence and fate of pharmaceutical and personal care products in the environment are of increasing public importance because of their ubiquitous nature and documented effects on wildlife, ecosystems, and potentially humans. One potential, yet undefined, source of entry of pharmaceuticals into the environment is via the land application of municipal wastewater onto permitted lands. The objective of the present study is to determine the extent to which pharmaceuticals are mitigated by or exported from man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 28 publications
6
37
1
1
Order By: Relevance
“…The majority of the study area of interest has been previously described (Birch et al, 2016; McEachran et al, 2016; Shifflett et al, 2014). Briefly, the study site is a 2000 ha, wastewater land-application facility which services a municipality of 70,000 defined by a large military presence and young (average age 22.8 years) population (United States Census Bureau, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the study area of interest has been previously described (Birch et al, 2016; McEachran et al, 2016; Shifflett et al, 2014). Briefly, the study site is a 2000 ha, wastewater land-application facility which services a municipality of 70,000 defined by a large military presence and young (average age 22.8 years) population (United States Census Bureau, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Prior data were included from August 2014 to January 2015 (McEachran et al, 2016) and are identified in the tables and figures below. Wastewater was collected from a central distribution spigot within the irrigation network and reflects wastewater after secondary treatment and storage in open reservoirs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We postulate the discrepancy is possibly due to a number of factors such as dilution of CECs, as they were acquired from the water by the plants or there was biodegradation of the chemicals occurring in the plant (51) or by photodegradation. However, recent studies have shown pharmaceutical concentrations in surface waters, which appear to remain constant over the course of several years (15,52,53). More studies would be needed to determine how CECs at concentrations found in reclaimed water for agriculture would interact with current IPM strategies (particularly pesticide application and use of beneficial insects), and how soil matrices would affect the chemical acquisition and translocation by plants.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 PPs have been detected in surface waters of 41 countries, 21 and it has been found that low-level chronic exposure to PPs can have adverse and sometimes unexpected effects on nontarget organisms. 22,23 Surface water concentrations of iron oxide nanoparticle (IONP) based MRI contrast agents, modelled using 25% and 50% market penetration (i.e., replacement of gadolinium-based MRI contrast agents), were estimated to be 3.1 ng L −1 and 8.4 ng L −1 for the years 2015 and 2020 respectively in Germany.…”
Section: Introductionmentioning
confidence: 99%